2022
DOI: 10.3389/fmicb.2022.893413
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Thermophysiology of Marine Synechococcus CRD1 Strains Isolated From Different Thermal Niches in Iron-Depleted Areas

Abstract: Marine Synechococcus cyanobacteria are ubiquitous in the ocean, a feature likely related to their extensive genetic diversity. Amongst the major lineages, clades I and IV preferentially thrive in temperate and cold, nutrient-rich waters, whilst clades II and III prefer warm, nitrogen or phosphorus-depleted waters. The existence of such cold (I/IV) and warm (II/III) thermotypes is corroborated by physiological characterization of representative strains. A fifth clade, CRD1, was recently shown to dominate the Sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Physiological measurement of temperature preferenda of strains belonging to clades I, II, III, IV, and V isolated across different latitudes further confirmed the existence of warm (clades II, III, V) and cold (clades I and IV) ‘thermotypes’ ( 38 42 ). Despite being phylogenetically distant, clades I and IV were further demonstrated to share a number of physiological adaptations to cold water, including a higher thermal sensitivity of phycobiliproteins ( 43 ), a similar change in membrane lipids ( 40 , 44 ) and an increase of the photoprotection capacities using the orange carotenoid protein (OCP; 45).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Physiological measurement of temperature preferenda of strains belonging to clades I, II, III, IV, and V isolated across different latitudes further confirmed the existence of warm (clades II, III, V) and cold (clades I and IV) ‘thermotypes’ ( 38 42 ). Despite being phylogenetically distant, clades I and IV were further demonstrated to share a number of physiological adaptations to cold water, including a higher thermal sensitivity of phycobiliproteins ( 43 ), a similar change in membrane lipids ( 40 , 44 ) and an increase of the photoprotection capacities using the orange carotenoid protein (OCP; 45).…”
Section: Introductionmentioning
confidence: 63%
“…2 ). While several strains belonging to clade I were previously shown to withstand colder temperatures than their tropical clade II counterparts ( 38 40 , 53 ), growth optima and boundary limits for temperature were only available for 1 clade IV ( 38 , 40 , 42 ) and 2 closely related clade III strains ( 38 , 40 , 41 , 54 ), and results were obtained in different light conditions, making them difficult to compare. Here, the direct comparison of clades I and IV strains, grown under the same conditions, showed quite similar thermal preferences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of gene gains or losses, and sequence divergence are thought to be responsible for the niche separation of Synechococcus ecotypes ( 27 ). For example, a genome comparison indicated that clade CRD1 has a larger collection of Fe-related genes than the other ecotypes, which helps it survive and succeed in low-iron habitats ( 27 , 28 ). It has also been reported that heterotrophy genes, such as bzt and potE (polar amino acid permease genes), are important for the survival of Synechococcus in harsh mesopelagic environments ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sub‐cluster 5.1 is mainly composed of pelagic marine strains and it is the most widespread lineage in the open ocean environment (Farrant et al, 2016). Extensive work combining global field observations, metagenomics, and physiological work with isolates has revealed a high genetic and functional diversity within this sub‐cluster and multiple genetic lineages (clades) have been identified (Doré et al, 2020; Farrant et al, 2016; Ferrieux et al, 2022; Mackey et al, 2017; Pittera et al, 2014; Six et al, 2021; Sohm et al, 2016). These lineages are physiologically specialized in different niches, revealing the existence of ecotypes defined by environmental factors such as temperature and light.…”
Section: Introductionmentioning
confidence: 99%